Comparative Analysis of Endodontic Instrument Separation, Secondary Errors and Retrieval Techniques in Private and Public Dental Hospitals - Hammad Hassan; Muhammad Ahmad; Mehvish Sajjad; Kanza Iqbal; Marij Hameed; Muhammad Hassan (Pakistan Journal of Medicine and Dentistry)
Background: Endodontic instrument separation and secondary procedural errors pose significant challenges in dental clinics. The study aimed to assess and compare the frequency of endodontic instrument separation, retrieval techniques and secondary procedural errors during retrieval in private and public dental hospitals in Punjab, Pakistan.